Sociological objects [ reconfigurations of social theory - Cooper, Geoff , 1953-; King, Andrew; Rettie, Ruth (Ashgate, 2009)
This volume interrogates the changing relationship between contemporary and classical sociology and the conceptual and theoretical foundations of the discipline. In three thematic sections, the book explores the conception of sociological objects, social practice, and social theory